2005
DOI: 10.1093/toxsci/kfi225
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Murine Host Response to Enteric Reovirus Infection by the Trichothecene Deoxynivalenol

Abstract: Based on the known capacity of deoxynivalenol (DON) to target gut lymphoid tissue and IgA production, it was hypothesized that this mycotoxin interferes with the immune response to enteric reovirus infection. When mice were orally gavaged, first with 25 mg/kg bw DON, and then with reovirus serotype 1, strain Lang (T1/L) 2 or 12 h later, viral titers in the GI tract were 10-fold higher than control mice after 5 days. Virus was almost completely cleared in both treatment and control groups from intestinal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 79 publications
6
50
0
Order By: Relevance
“…When administered to monogastric animals, DON elicits a specific immune response which is manifested by increased Th2 activity and a drop in Th1 activity (Li et al 2005), as found in allergies (Luft et al 2008, Maresca andFantini 2010). A similar scenario is observed in rumen dysfunctions where DON acts as an antibacterial agent.…”
Section: Discussionmentioning
confidence: 85%
“…When administered to monogastric animals, DON elicits a specific immune response which is manifested by increased Th2 activity and a drop in Th1 activity (Li et al 2005), as found in allergies (Luft et al 2008, Maresca andFantini 2010). A similar scenario is observed in rumen dysfunctions where DON acts as an antibacterial agent.…”
Section: Discussionmentioning
confidence: 85%
“…Numerous studies have demonstrated that selected mycotoxins affect the Th1/Th2 balance. Li et al (2005) observed that doxynivalenol administered to mice activated Th2 populations and inhibited the Th1 immune response. Subclinical doses of patulin can alter the Th1/Th2 balance in favor of the Th2 immune response and promote allergic reactions and ulcerative colitis (Luft et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, consumption of feed contaminated with T-2 toxin, another trichothecene, increased the susceptibility to Herpes simplex virus-1 (HSV-1) infection, by allowing virus proliferation, ultimately resulting in the death of mice naturally resistant to HSV-1 (Friend et al, 1983). Other studies in mice suggests that DON compromised resistance to enteric (Li et al, 2005) and respiratory (Li et al, 2007) reovirus infection.…”
Section: -Introductionmentioning
confidence: 98%